"Double Frozen Transfer" Could Influence the Perinatal and Children's Growth: A Nested Case-Control Study of 6705 Live Birth Cycles - Gao, Jie; Zhang, Yiyuan; Cui, Linlin; Zhang, Tao; Wu, Bingjie; Gao, Shanshan; Chen, Zi-Jiang (Frontiers in Endocrinology, 2022)
Objective To evaluate the neonatal, and children growth outcomes of cryotransfer of embryos developed from frozen gametes（double frozen transfer）. Methods This nested case-control study included 6705 women who had a singleton live birth after embryo transfer at the Center for Reproductive Medicine, Shandong Provincial Hospital Affiliated to Shandong University from 2008 to 2020. 745 women underwent frozen embryo transfers developed from frozen gametes (double frozen transfers, DFTs). Propensity score methodology was used to balance the two groups by maternal age and BMI before evaluating outcomes. After age and BMI matched with propensity score methodology in a ratio of 1:4, the control groups enrolled 2980 women underwent fresh embryo transfers (ETs) and 2980 women underwent frozen embryo transfers (FETs) from fresh gametes. The born children were followed to at least 5 years old, and some of them were followed up to 10 years. Neonatal outcomes and childhood growth measurements were compared among the three groups. Results The average birth weight of DFTs group (3462g) was significantly higher compared to FETs group (3458g) and ETs group (3412g). The rates of large for gestational age (LGA) babies in DFTs and FETs groups were higher than ETs group (30.9%vs.24.8%; 29.4%vs.24.8%, respectively). After adjusted for different confounders combination in three models, the birth weight, risk of LGA in DFTs and FETs groups were still higher than ET groups. In multiple linear regression analysis of the children's development, the height Z-score of children born from DFTs and FETs groups were higher than children from ETs However, childhood growth measurements including body weight Z-score and BMI Z-score were not significantly different among three groups. In addition, the proportion of male children born from the DETs was more than that from ETs. Conclusions There is an increased risk of large for gestational age babies associated with pregnancies conceived from double frozen transfer. Children are inclined to be higher in the future in this group than frozen embryo transfer. The related etiology and pathophysiology mechanisms still need to be revealed. In the future, well-designed, observational studies with in-depth collection of patients’ characteristics may shed more light on this issue.